(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The purpose of this article is to outline some of the most common terminological issues that audiovisual translators encounter when translating science films. These difficulties include term recognition, term comprehension, appropriate equivalent selection, handling inadequate equivalents, denominative variation resolution, selecting between in vivo and in vitro terminology, and resolving mistranscriptions